2014
DOI: 10.1177/0192513x14560642
|View full text |Cite
|
Sign up to set email alerts
|

Parenting Stress Among Low-Income and Working-Class Fathers

Abstract: Contemporary norms of fatherhood emphasize the dual demands of breadwinning and daily involvement in childcare. Recent qualitative research suggests that working-class fathers find it difficult to meet these demands due to job instability and workplace inflexibility. Yet, little quantitative research has examined how employment characteristics are related to fathers’ parenting stress, in comparison with mothers’. Analyses using data from the Fragile Families and Child Wellbeing Study (N = 3,165) show that unem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
3
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(95 citation statements)
references
References 55 publications
4
85
3
3
Order By: Relevance
“…The analysis revealed a complete mediation effect of parenting stress in the relationship between work-family conflict and depression among single parents. These results were in line with existing literature [ [7], [10]]. However, these results differed from one existing study [3], which asserted that there was a significant influencing relationship between work-family conflict and depression.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The analysis revealed a complete mediation effect of parenting stress in the relationship between work-family conflict and depression among single parents. These results were in line with existing literature [ [7], [10]]. However, these results differed from one existing study [3], which asserted that there was a significant influencing relationship between work-family conflict and depression.…”
Section: Discussionsupporting
confidence: 84%
“…Existing studies also support the relationship between work-family conflict and stress and between stress and depression. Nomaguchi and Johnson [10] asserted that work-family stress has a significant influence on the parenting stress, and Lee, Chun, Jeon, and Chung [7]reported that the parenting stress experienced by low-income mothers has a significant influence on depression.…”
Section: Introductionmentioning
confidence: 99%
“…The measures for our study included baseline variables (i.e., measured just after the child's birth and typically time invariant), change over Year 1 variables (i.e., change scores formed from Year 1 value – baseline value), and time‐varying variables over Years 1–5. Many of our measures were commonly used scales that were formed from subsets of questions within the Fragile Families Questionnaire (see, e.g., Bronte‐Tinkew et al, ; Knoester et al, ; McLanahan & Carlson, ; Nomaguchi & Johnson, ; Reichman et al, ). Indeed, the FFCW expressly sought to achieve high levels of reliability and validity in its measures by drawing from well‐established questions that were also used in other surveys (e.g., Early Head Start, Early Childhood Longitudinal Study—Birth Cohort).…”
Section: Methodsmentioning
confidence: 99%
“…Fathers who are older, White, employed, higher earning, well educated, and able to rely on instrumental support were expected to be less likely to experience parenting stress. They may be more mature, not subject to discrimination, established in their careers, and in possession of resources that can allow them to more easily meet the financial and domestic care demands of parenting (Bronte-Tinkew, 2007;Cunningham & Knoester, 2007;Nomaguchi & Johnson, 2014;Thoits, 2010).…”
Section: Father-specific Coparenting and Child-specific Contextual mentioning
confidence: 99%
See 1 more Smart Citation